Eutrofização em reservatórios - Estudo de caso : reservatórios de Rio Bonito e Suíça (ES) - Araujo, Daniela Rodrigues (2016)
Rio Bonito and Suíça hydropower plants reservoirs, located in Santa Maria da Vitoria river watershed, one of the main water supply sources for Great Vitória Metropolitan Region, Espírito Santo State, Brazil, receive the nutrient loads originated from sanitary sewage, agricultural fields and chicken farms. The study aimed to analyze reservoirs water quality and eutrophication aspects considering results from monitoring campaigns conducted between October 2008 and July 2014. Reservoirs trophic status classification was carried out through application of Salas and Martino (1991) and OECD (1982) models and Carlson (1977), Toledo (1984), Lamparelli (2004) and Cunha (2012) Trophic State Indexes (TSI) models. Morphoedaphic indexes were calculated to estimate reservoirs phosphorous loads reductions needed for the maintenance of mesotrophic conditions. The trophic classification results for Rio Bonito and Suíça reservoirs through the application of different models and TSIs indicated that the resulting classes may be very different even if obtained from parameter values recorded at the same point in the same campaign. The qualitative and quantitative results from the application of Cunha EIT were close to the Lamparelli than those obtained by using the others models and EITs. Values obtained by Morphoedhaphic indexes estimation indicated the necessity of phosphorus loads reduction for maintaining mesotrophic conditions in the reservoirs. The fact that Suíça reservoir is located downstream of Rio Bonito reservoir led to its classification in degrees and trophic classes generally lower than those corresponding to the latter, considering same models and parameters, probably because the Rio Bonito reservoir is functioning as a kind of rough wastewater treatment plant, causing reduction of the pollution load flowing into the downstream reservoir. It was also concluded that there is significant influence of seasonality and rainfall on t trophic classes estimates.